Gambaran Darah Kambing Gembrong, Kambing Peranakan Etawah, dan Kambing Kacang di Bali (BLOOD ILLUSTRATION OF GEMBRONG GOAT, ETAWAH CROSSBRED GOAT AND KACANG GOAT IN BALI) - Yupardhi, Wayan Sayang; Oka, I Gusti Lanang; Mantra, Ida Bagus; Suyasa, I Nyoman; Suranjaya, I Gede (Jurnal Veteriner, 2015)
There were three kinds of goat developed in Bali since a long time ago i.e. Gembrong goat, EtawahCrossbred goat, and Kacang goat. Gembrong goat is nearly disappearingrecently due to decrease of itspopulation from year to year. The Gembrong goat has very interesting performance, funny, and this speciesis Balinese native goats. The objective of thisexperiment was to know the blood illustration among thethree speciesof the Balinese native goatwhere in the future it can be used as a guide to develop each ofthem. The experiment was used nine adults goats namely three adult male Gembrong goats, three adultmale Etawah Crossbred goats, and three adult male Kacang Goats respectively. The animal fed dailygreen feed grows around them and additional rice bran. Blood samples of the animals were collected forabout10-15 mL each with venoject, and then was kept in a cooler box and subsequently sent to the ProdiaClinic Laboratory at Denpasar. The results of the experiment showed that blood illustration of the threekinds of goat was not significantly different (P > 0.05) except the triglyseride.
Keywords: gembrong goat, etawah crossbred goat, kacang goat, blood components